Pengembangan Media Pembelajaran E-Modul Bank Dan Sistem Pembayaran Berbasis Android Untuk Peserta Didik Kelas X - Kiki Wijayanti; Muhammad Abdul Ghofur (Jurnal Pendidikan Ekonomi, 2021)
This development research carried out against the lack of understanding of the material in students in economics. The purpose of this development research is to increase students' understanding through the use of e-module learning media based on android. This research uses research and development (R&D) with ADDIE models. The research design used is the One Group Pre-test-Post-test Design with research subjects in class X IPS students for testing android based e-module learning media products. The results of limited trials as part of the development phase have received excellent results. Students' understanding was measured using gain score analysis which obtained a value of 0.57 with moderate criteria. There are significant differences in the test results between before and after using e-modules in student learning.DOI: https://dx.doi.org/10.17977/UM014v14i12021p001